The implementation of English Language Assessment Based on Language Assessment and Evaluation Principles at Senior High School - Amos Frans Abdial Tarigan; Palti Hansd Togi Maruhum Simanjuntak; Cassandra Dealova Sitopu; Jonathan Hartodes Purba; Dumaris E. Silalahi (JURNAL PENDIDIKAN BAHASA, 2025)
This study investigates the implementation of English language assessment based on five core language testing principles: practicality, reliability, validity, authenticity, and washback. The research was conducted at SMA N 1 Siantar, involving 25 eleventh-grade students. A mixed-method approach was applied, combining quantitative data from test scores (multiple-choice and essay) with qualitative insights from observation and rubric-based evaluation. The results show that the assessment was feasible and manageable in the classroom setting. Reliability was high for most components, although the listening section revealed weaknesses in validity. Authentic tasks increased student engagement, while positive washback was observed through enhanced teaching practices and student motivation. These findings demonstrate that principled language assessment, when integrated into the classroom context, can meaningfully support student learning and teaching effectiveness. However, challenges related to item construction and classroom logistics suggest the need for further refinement in future implementations.